Coelomycetes of Assam-II - U.N. SAIKIA, M.S. ALI and (Indian Phytopathology, 2002)
Out of the ten species of Phomopsis described in this paper, three, viz, P. clerodendrumii, P. peperomiae and P. zingiberii recorded on Clerodendrum splendidum, Peperomia sp. and Zingiber officinale respectively are new to science. While P. corchoricola, P. phaseoli, Phomopsis state of Diaporthe phaseolorum var. batatatis and P. tersa have not so far been reported from India. Moreover, P. capsici, P. palmicola and P. vexans recorded on Capsicum annuum, Areca catechu and Solanum me/ongena have been described with additional characters hitherto unkown on these fungi.